UPAYA PENINGKATAN KUALITAS PAUD PUTIH MELATI KELURAHAN MERGOSONO KECAMATAN KEDUNGKANDANG MALANG MELALUI PENDIDIKAN ANAK USIA DINI DAN PENINGKATAN KUALITAS PENDIDIK - Nilawati Fiernaningsih; Baroroh Lestari; Farika Nikmah; Achmad Zaini; Yosi Afandi (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2019)
Based on the results of the discussion it was found that the Pos PAUD Putih Melati manager experienced obstacles in terms of financial management and administration. Therefore, dedication was carried out in the form of providing material related to the management and financial administration of Pos PAUD Putih Melati. Overall, the service activities carried out at the Pos PAUD Putih Melati can be said to be successful. This success is not only measured by the four components above, it can also be seen from the participants' satisfaction after participating in the activities and the use of APE by students of the Pos PAUD Putih Melati. Based on the results of the implementation of the dedication that has been carried out, several suggestions can be submitted, namely: 1) The time of the implementation of the service activities needs to be increased so that the objectives of the activity can be fully achieved. 2) The existence of follow-up activities in the form of similar training is always held periodically so as to improve the ability of teachers to carry out the teaching and learning process.